The linguistic image of the word (Words) in the statements of Archbishop Grzegorz Ryś - Laskowska, Elżbieta (The Bible as a meeting place for Christian denominations, 2022)
The chapter is devoted to research situated in the area of the linguistic image of the world. The subject of the study is the word, and the aim is to determine its meanings and semantic shades in the religious discourse. The research material consists of the statements of Archbishop Grzegorz Ryś, published in the book entitled The Power of the Word (2016). As a result of the analyzes, it was found that the lexeme „word” is used in the sense of a unit of the language system, also as a text. These meanings are common to different varieties of language, including colloquial. Two meanings of „the Word” are specific to religious discourse: as the Bible and as an event crowned by Jesus Christ. The article established the boundary of the linguist’s activities in the matter under study, at the same time indicating theologians as researchers who could continue their research.